Temperature-dependent Methanogenesis Model - Kehua You (Zenodo, 2023)
This is a temperature-dependent methanogenesis model associated with a manuscript ( Biodegradation of Ancient Organic Carbon Fuels Seabed Methane Emission at the Arctic Continental Shelves )to be submitted to the Journal of Geophysical Research - Global Biogeochemical Cycles. It is written in MatLab. It is the Introductory Carbon Balance Model (ICBM) ( Andrén & Kätterer, 1997 ). In this model, the total organic carbon falls into two pools, the labile pool with a relatively high reactivity and a stable pool with a relatively low reactivity. A fraction of the degrading material from the labile pool flows into the stable pool representing humification. The remaining part leaves the system as CH 4 and CO 2 . Biodegradation at the reference temperature 4 oC is described in the file "plot_methane_production". The file "plot_temperature_response" describes how the reactivity of the organic carbon changes with temperature. Detailed information about the model could be found in the paper Biodegradation of Ancient Organic Carbon Fuels Seabed Methane Emission at the Arctic Continental Shelves.